Initial Experience of Minimally Invasive Gastrectomy for Gastric Cancer in Vilnius University Hospital Santaros Klinikos and National Cancer Institute: Clinical Case Series and Literature Review - Lukšta, Martynas; Sasnauskas, Gustas; Baušys, Augustinas; Rybakovas, Andrius; Kuliavas, Justas; Baušys, Rimantas; Strupas, Kęstutis (Lietuvos chirurgija, 2021)
Background. Gastric cancer remains one of the most common cancers in Lithuania and Worldwide. Surgical treatment is the only potentially curative treatment option for it. Historically open gastrectomy was considered as the gold standard approach. Although, the development of minimally invasive surgery and accumulation of the clinical data has led to the adoption of minimally invasive gastrectomy. Clinical cases. We present a series of 8 clinical cases who underwent minimally invasive surgery for early or locally advanced gastric cancer in Vilnius University Hospital Santaros Klinikos and the National Cancer Institute. Discussion. Large scale randomized controlled trials in Asia have proved that laparoscopic surgery is safe and oncologically effective for clinical stage I distal gastric cancer. The increasing amount of data supports the safety of minimally invasive gastrectomy for advanced or proximal gastric cancer. Most of the trials performed in Asia confirmed, that laparoscopic gastrectomy has some advantages, including: decreased blood loss, decreased postoperative pain, and morbidity. Recent randomized controlled trials of Western countries proved the safety of laparoscopic gastrectomy and the comparable 1-year long-term outcomes. Although, they failed to show improved recovery after minimally invasive surgery. Currently, there is sufficient evidence to adopt minimally invasive gastrectomy for gastric cancer into routine clinical practice in Lithuania. Conclusions. The first experience of minimally invasive gastric cancer surgery in Vilnius University Hospital Santaros Klinikos and the National Cancer Institute was successful. All gastrectomies were radical, and without major postoperative complications.
Keywords: gastric cancer; minimally invasive surgery; literature review